FACTORS CAUSING THE INCIDENCE OF HYPERTENSION IN THE ELDERLY IN SIDOMULYO HAMLET RT 52 RW 15 SRAGEN WETAN SRAGEN - Hwarti, Rina (Jurnal AKPER GSH, 2021)
According to WHO (1978), the limit of blood pressure that is still considered normal is 140/90 mmHg and blood pressure equal to or above 160/95 is considered hypertension. The systolic pressure continues to increase until the age of 80 years and the diastolic pressure continues to increase until the age of 55-60 years, then decreases slowly The purpose of this study was to determine the causes of hypertension in the elderly in Sidomulyo Hamlet RT 52 RW 15 Sragen Wetan Sragen. This study used a quantitative study with a survey research design and a cross sectional approach. The population in this study were all elderly aged> 40 in Sidomulyo hamlet RT 52 RW 15 Sragen Wetan Sragen as many as 40 people, with saturated sampling, namely all elderly> 40 in Sidomulyo hamlet RT 52 RW 15 Sragen Wetan Sragen. The instrument used in this study was a questionnaire in the form of a single "yes" and "no" checklist. . The validity test used the Pearson Product Moment formula and the reliability test used Cronbach alpha. And statistical test using frequency distribution. Based on the results of the study, it was found that the elderly in Sidomulyo Hamlet RT 52 RW 15 Sragen Wetan Sragen, from the research results found that the most common causes of hypertension are food, lack of exercise and a lot of smoking. And the advice given is to make the Posyandu more active